A survey of methods for discrete optimum struct ural design - Bauer, Jacek (Computer Assisted Methods in Engineering and Science, 1994)
The available methods and solutions of problems in discrete optimum structural design are reviewed. They are classified into the following categories: branch and bound methods, dual approach, enumeration methods, penalty function approach, simulated annealing and other methods. For the majority of problems, none of the methods is guaranteed to give the exact solution from the mathematical point of view. However, "good practical" solutions can be obtained at an acceptable cost.